Use of Physical Test Measurements for Hockey Sports Using the Physical Education Sports and Health Application for Extracurricular Students of Senior High School Muhammadiyah 6 Palembang - Nadila Tri Agustin; Hartati; Silvi Aryanti (Journal of Physical Education Health and Sport, 2024)
The study entitled The Use of Physical Test Result Measurement in Hockey Sports Branch Using PE Application on Extracurricular Students of Muhammadiyah 6 High School Palembang. This study aims to determine the physical condition of hockey sports students using the help of PE application on extracurricular students of Muhammadiyah 6 High School Palembang. The research method used in this study is quantitative descriptive method. The results of the study were to produce data on the physical condition of extracurricular students of Muhammadiyah 6 High School Palembang with a very good category of 16.64%, a good category of 13.58%, a sufficient category of 92.9%, a less category of 89.2% and a very less category of 29.98%. The implications of the results of this study are the growing awareness for students to continue to improve and maintain their physical condition wherever and whenever, so that they can improve the physical condition of students in the sufficient, less and very less categories so that they become better.